Power spectral analysis of heart rate variability in Bangladeshi healthy population of different age (Bangladesh Journal of Physiology and Pharmacology, 2014)
Heart rate variability (HRV) has been considered as an indicator of autonomic nerve function status. We aimed to find out the reference values of heart rate variability by power spectral analysis in our healthy population of different age. This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from the period of July 2012 to June 2013. For this, 180 subjects were selected with the age ranging from 15-60 years. All the study subjects were divided into 3 different groups according to age (Group A: 15-30 years; Group B: 31-45 years; Group C: 46-60 years). Each group contained 60 subjects of which 30 were male and 30 were female. The subjects were selected from different areas of Dhaka city by personal contacts. Analysis of HRV parameters were done in Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. For statistical analysis, one way ANOVA, unpaired Students t-test and Pearsons correlation coefficient test were performed by using SPSS (version-17) as applicable. LF nu, LF power and LF/HF were significantly (p